Giant Muscle Lipoma: an Exception to Oncologic Treatment Criteria in Soft Tissue Tumors - Tchekmedyian, Vartan; Geninazzi, Héctor; Ricciardi, Norma; Aguirre, Carlos (Cirugía del Uruguay, 1981)
In case of lipomas that fullfill clinic and pathologIcal criteria if possible to avoid oncologic treatment when it implies amputation or severe functional impairement. But with a high rate of local recurrences, it is a benign lesion that don't give metastasis or kilI the patient.